THE EFFECT OF FREE CASH FLOW ON ASSET UTILIZATION WITH OWNERSHIP STRUCTURES AS MODERATING VARIABLES - Elizabeth Nathania; Samuel Putera; Siti Farhana; Wijantini Wijantini (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2019)
This study aims to examine how free cash flow (FCF) affects on asset utilization (AU) as a proxy for agency cost, followed by investigating the influence of ownership structures as moderating variables in reducing the negative effect of FCF on asset utilization. The research sample of 465 companies consisted of all companies listed on the Indonesia Stock Exchange in 2013-2017 with purposive sampling method. The findings of this study showed that FCF negatively influences AU). Institutional ownership weakens the negative relationship between FCF and AU. Contrarily, managerial ownership strengthens the negative relationship between FCF and AU. This study also found that family ownership strengthens the negative relationship between FCF and AU. This study contributes to understanding the role of various ownership structures in utilizing company's resources to improve their asset utilization, especially in the family ownership that dominates Indonesian firms.